European Memories of the Second World War - Peitsch, Helmut; Burdett, Charles, 1966-; Gorrara, Claire (Berghahn Books, 2006)
During the fifty years since the end of hostilities, European literary memories of the war have undergone considerable change, influenced by the personal experiences of writers as well as changing political, social, and cultural factors. This volume examines changing ways of remembering the war in the literatures of France, Germany, and Italy; changes in the subject of memory, and in the relations between fiction, autobiography, and documentary, with the focus being on the extent to which shared European memories of the war have been constructed.